Organizational, Legal and Methodological Issues of Forensic Ecology in the EAEU Countries - N. V. Mikhaleva (Теория и практика судебной экспертизы)
The article addresses the current state of forensic ecology in the Republic of Kazakhstan, the Republic of Armenia, and the Republic of Belarus. The author has analyzed the relevant publications and the data of the oﬃcial websites of forensic organizations conducting this type of forensic examination. The article presents the methods used by forensic ecologists, highlights the problems they face.The paper also reveals the unequal level of forensic ecology in Kazakhstan, Armenia, and Belarus; simultaneously, it shows that the need for its improvement is recognized in all these countries. Finally, the author notes that for such a development, mutual exchange of experience is essential, as well as the validation of methodological materials developed primarily in the Republic of Kazakhstan and the Russian Federation, with a view to their application in other countries of the Eurasian Economic Union, especially when conducting forensic examinations in cases related to the cross-border negative anthropogenic impact on environmental objects.